Targeting Chromatin Readers - James, LI (Clin Pharmacol Ther, 2013)
Modulation of gene expression through epigenetic signaling has recently emerged as a novel approach in treating human disease. Specifically, chromatin reader proteins, which mediate protein–protein interactions via binding to modified lysine residues, are gaining traction as potential therapeutic targets. Herein, we review recent efforts to understand and modulate the activity of chromatin reader proteins with small-molecule ligands.